Hexafluoro‐2‐propanol Promotes para‐Selective C–H Amination of Free Anilines with Azodicarboxylates. Issue 32 (25th August 2017) - Tang, Ren‐Jin; Milcent, Thierry; Crousse, Benoit
Abstract : An effective, mild, and clean method for the C–H amination of free anilines with azodicarboxylates in 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐propanol (HFIP) without the need for any additional catalysts or reagents was developed. The reaction was found to be highly regioselective and provided a series of p ‐aminophenylhydrazine derivatives in excellent yields. Moreover, compatibility with a free amino group makes this protocol an attractive strategy in synthetic chemistry. Abstract : An effective, mild, and clean method for the C–H amination of free anilines with azodicarboxylates in 1, 1, 1, 3, 3, 3‐hexafluoro‐2‐propanol (HFIP) without the need for any additional catalysts or reagents is described. The reaction is highly regioselective in that the amination proceeds at the para position of anilines to provide p ‐aminophenylhydrazine derivatives in excellent yields.